التسويق و حماية حقوق المستهلك - معيوف, هدى (Sciences humaines, 2014)
إن الوضع اليوم في السوق الجزائرية يعد أفضل حالا مما كانت عليه من الناحية النظرية, فالعمل على إصدار القوانين الكفيلة بحماية المستهلك ووجود جمعيات لحماية المستهلك كلها تعد خطوة في مشوار الألف ميل إلا أن هذا لا تكفي لتحقيق الحماية المنشودة في السوق الجزائرية إذ يتطلب الأمر تفعيل دور الجهات الرسمية وغير الرسمية لدفع منظمات الأعمال للقيام بواجبها تجاه مسؤولياتها الاجتماعية والتي من ضمنها  حماية حقوق المستهلك        The situation today in the Algerian market is better off than it was in theory, the work to pass laws to protect the consumer and the presence of associations for consumer protection are a step in the journey of a thousand miles but this is not sufficient to achieve protection objectives in the Algerian market as it is required to activate the role official and unofficial organizations to drive business to do their duty towards their social responsibilities, which include the protection of consumer rights.